Elasticity tensor inversion from spherical sample measurements - Nadri, D.; Bona, Andrej; Brajanovski, Miroslav (EAGE, 2009)
From the P-wave traveltime measurements over a spherical shale sample at 40 MPa we find the symmetry axis. We transform the ray velocities from the measurement coordinate system to the symmetry axis coordinate system. Assuming transverse isotropy symmetry, we estimate the elasticity tensor using a very fast simulated annealing algorithm followed by a quasi Newton method.